Moisture Sorption and Thermodynamic Properties of Wood under Dynamic Condition - Tiantian Yang; Erni Ma (International Journal of Polymer Science)
Thermodynamic approach is a useful method to study interactions between water and wood at molecular level. This work investigated the dynamic moisture sorption and thermodynamic properties for two thick poplar woods (Populus euramericana Cv.) subjected to sinusoidal relative humidity (RH) changes between 45% and 75% for cyclic period of 1, 6, and 24 h, at two temperatures of 25°C and 40°C. Moisture changes of the specimens were measured during the successive adsorption and desorption processes, giving the following results: (1) moisture content changed sinusoidally with the imposed RH and was inversely related to specimen thickness as well as temperature, but in a positive correlation with cyclic periods; (2) all of QL, ΔG, and TΔS of the adsorbed water during dynamic sorption decreased with increasing moisture content or specimen thickness and decreasing cyclic period. However, temperature had opposite effects on ΔG and TΔS. (3) Both moisture sorption hysteresis and thermodynamic sorption hysteresis could be found. The former became weak with rising temperature or thicker specimens, while the latter got clear when temperature or specimen thickness increased.